DEVELOPMENT OF COHERENT SPEECH OF YOUNGER CHILDREN PRESCHOOL AGE (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The article reveals the features of the development of coherent speech of younger preschoolers; conditions, methods, techniques of their development.